2019
DOI: 10.1039/c9sc03693h
|View full text |Cite
|
Sign up to set email alerts
|

Photo-cleavable purification/protection handle assisted synthesis of giant modified proteins with tandem repeats

Abstract: Proteins with tandem repeats have essential physical or biological roles in cells and have been widely investigated as biomaterials or vaccines. Chemically derived proteins with tandem repeats would be beneficial for research, owing to their accurate structures, possibly with precise modifications, produced by chemical synthesis. Traditional protein synthesis often leads to severe handling loss due to multiple ligations and HPLC purifications. To improve the protein synthesis efficiency, we developed a purific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…[8d] An acetylated O-linked Thrg lycosyl amino acid 10 was prepared following previous protocols and employed directly in Fmoc-SPPS. [18] After one-flask aspartylation and subsequent deacetylation of O-glycan using 10 % aqueous hydrazine,followed by single reversed-phase HPLC purification, the desired glycopeptide 16 was isolated at 52 % yield over three steps.Thus,four glycopeptides III (fragments R319-L335, 13-16)w ere efficiently synthesized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8d] An acetylated O-linked Thrg lycosyl amino acid 10 was prepared following previous protocols and employed directly in Fmoc-SPPS. [18] After one-flask aspartylation and subsequent deacetylation of O-glycan using 10 % aqueous hydrazine,followed by single reversed-phase HPLC purification, the desired glycopeptide 16 was isolated at 52 % yield over three steps.Thus,four glycopeptides III (fragments R319-L335, 13-16)w ere efficiently synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the structure of the Tn‐Thr antigen is important for molecular recognition due to its effect on peptide conformation [8d] . An acetylated O‐linked Thr glycosyl amino acid 10 was prepared following previous protocols and employed directly in Fmoc‐SPPS [18] . After one‐flask aspartylation and subsequent deacetylation of O‐glycan using 10 % aqueous hydrazine, followed by single reversed‐phase HPLC purification, the desired glycopeptide 16 was isolated at 52 % yield over three steps.…”
Section: Resultsmentioning
confidence: 99%
“…To save on the labors and the severe handling loss due to multiple rounds of HPLC purifications, an N‐terminal bifunctional protection/purification handle (PPH) was developed (Figure 10A). [ 71 ] The handle was designed to serve dual roles: a photo‐ labile linker basically works as a temporary protection of N‐terminal Cys, and a His6 tag allows for quick and easy purification of the peptide fragments via immobilized metal affinity chromatography (for example, Ni‐NTA beads). A pH switch was installed, which enabled facile loading and elution of the peptide by adjusting the pH under mild conditions (pH 7.0 to 3.0).…”
Section: Methods Development Towards Efficient Assembly Of Glycoproteinsmentioning
confidence: 99%
“…A common theme of the solid-phase synthesis tactics used to access fragments for ligation is that Fmoc-Thr(αAc 3 GalNAc) building blocks were coupled by using a twofold excess. 30–32 Considering the reported difficulties, 12 this number of excess equivalents is small. Possible truncations, side reactions, and purity of the products prior to purification have not been reported.…”
Section: Introductionmentioning
confidence: 99%